Outcomes of the paired kidney transplantation - Silva, Ana Carine Goersch (2017)
Purpose: We aimed to assess kidney transplant (KT) outcomes in paired kidney recipients and analyzing the risk factors for inferior outcomes. Methods: single center retrospective study including all deceased donor KT performed in 2014 in which both kidneys were transplanted into our patients. Patients were divided in two groups according to the laterality of the transplanted kidney. The following outcomes were assessed: delayed graft function (DGF), acute rejection, graft loss, death, glomerular filtration rate (GFR) and incidence of the composite endpoint of loss, death or GFR<50 mL/min at 2 years. Risk analysis was performed by using binary logistic regression. Results: Donors were predominantly young (29+14 years) men (71%) who died because of head trauma (70%). Only 2 (6%) were expanded criteria donors. Demography of KT recipients were similar between groups: men (77 vs. 57%, p=0.126), young (35+20 vs. 37+17 years old, p=0.668), with unknown etiology for chronic kidney disease (31 vs. 40%, p=0.179), who were 31+37 months (27+25 vs. 36+47 months, p=0.311) on dialysis before KT. 7% were retransplants (9 vs. 5%, p=0.309) and Class I and II PRA were 6 20% (9+23 vs. 10+19%, p=0.907) and 9+20% (9+25 vs. 5+15%, p=0.476), respectively. The mean cold ischemia time was 25+9 hours (24+9 vs. 27+9 hours, p=0.269) and 66% (66 vs. 66%, p=1.000) were pumped into a pulsatile perfusion machine. All patients were induced with antithymocyte globulin, 52% (54 vs. 49%, p=0.808) received tacrolimus and everolimus as initial immunosuppressive regimen, and 62% were steroid-free (69 vs. 54%, p=0.319). There were no differences between groups on the incidence of DGF (20 vs. 32%, p=0.282), acute rejection (0 vs. 11%, p=0.054), graft loss (0 vs. 6%, p=0.493), death (6 vs. 6%, p=1.000), GFR (71 28 vs. 72 37 mL/min, p=0.877) or on the incidence of the composite outcome of graft loss, death or GFR <50 mL/min at 2 years (29vs. 23%, p=0.785). In multivariate analysis, DGF was the variable independently associated to the composite outcome (OR 4.120, 95% CI 1.194-14.271, p=0.025). Conclusion: In this cohort of paired kidney transplants with optimum donors, DGF was the only risk factor for inferior outcomes.